PENGARUH KUALITAS PELAYANAN DAN FASILITASTERHADAP KEPUASAN KONSUMEN ASTON HOTEL DI KOTA BATAM - Adetami; Hikmah (LPPM Universitas Putera Batam, 2022)
One of the most important factors to consider when the competition is getting tougher is the quality of services and facilities. Competitive hotels offer various facilities that attract customers' attention and provide quality services to increase guest satisfaction and comfort. In addition to the inadequate quality of service and facilities, customers move to different hotels. The purpose of this research is to use accidental sampling technique to analyze how the quality of service and equipment affects customer satisfaction at Aston Hotel Batam City. That is, data were collected from 192 respondents who were distributed in the form of a questionnaire. In this study, testing data quality using reliability and validity tests, classical assumption tests, and classical hypothesis testing. Multiple linear regression analysis and coefficient of determination (R2) were used in this study. Then the research hypothesis was tested by F-test and t-test with SSPS version 25. The results obtained by the decision coefficient (R2) is the difference between service quality and installation effectiveness for customer satisfaction 57.1%. From the F test and T test it can be concluded that the quality of service and facilities has a positive correlation on customer satisfaction.